Self-Driving Vehicles and Their Impact on the European Convention on Human Rights - Habil Csongor Herke; Szabó, Barbara (Journal of Human Rights, Culture and Legal System, 2024)
The integration of artificial intelligence (AI) into criminal justice systems has grown rapidly, offering significant potential to enhance efficiency and decision-making. However, this advancement also raises ethical and legal concerns, such as data privacy violations, algorithmic bias, and transparency in AI-driven processes. This research examines the legal and ethical implications of AI in criminal justice, focusing on its applications in law enforcement and judiciary systems. Through a normative legal analysis, employing statutory, conceptual, and comparative legal approaches, the study draws insights from the European Convention on Human Rights (ECHR) and international literature. The findings highlight societal apprehensions regarding autonomous systems, inadequacies in current legal frameworks, and ethical challenges in programming AI for decision-making. These challenges include ensuring privacy, data protection, and adherence to fair trial principles. The study concludes that prudent legal regulations are crucial for ensuring responsible and ethical deployment of AI in criminal justice systems. Ultimately, the research emphasizes the importance of balancing technological innovation with the protection of fundamental human rights, contributing to a framework for the ethical and sustainable integration of AI into legal systems globally.